Report of the Diephuis workshop on the environmental aspects of dredging held at HR Wallingford, UK, December 1990. (Thomas Telford, 1990)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Report of the Diephuis workshop on the environmental aspects of dredging held at HR Wallingford in December 1990.